Pengaruh Leader Member Exchange (LMX) dan Efikasi Diri terhadap Kinerja Karyawan: (Studi Kasus pada RS. Dian Husada Mojokerto) - Wiranti, Siska; Baidlowi, Imam; Hadi Poernomo, Agoes (Politeknik Kampar, 2024)
The relationship between the leader and team members takes place in a one-on-one relationship, where each team member has a unique relationship with the leader. Transparency and fairness are increasingly appreciated, leaders who apply the Leader Member Exchange (LMX) principle can create a fair work environment and increase self-efficacy. A level of self-efficacy that is too high can cause individuals to become overconfident and not calculate risks adequately, resulting in a decline in employee performance. This research aims to determine the influence of Leader Member Exchange (LMX) and Self-Efficacy on Employee Performance at Dian Husada Hospital, Mojokerto. This research was conducted by distributing questionnaires online using Google Form to employees of Dian Husada Hospital, Mojokerto. The population of this study was 50 people with a sample of 50 people using a saturated sample. Data processing techniques were carried out using the SPSS 29.0 program. with the research results showing that there is a positive and significant influence of the LMX variable on performance, the Self-Efficacy variable on Performance, then the LMX and Self-Efficacy variables on employee performance at Dian Husada Hospital Mojokerto.